Role Playing: An Effective Strategy for Understanding Muhammadiyah's Social Enterprises in Grade XII at Muhammadiyah High School Bumiayu - Harkatiningsih, Wise Masja Lintang; Rifki Zahrani Masyithoh; Dwi Septina Anggraeni; Darojat (Insight School Academy, 2025)
Introduction to the Problem: Education plays a crucial role in enhancing human resource quality, in line with the national education goals aimed at advancing the nation's intellectual life. One organization that has made significant contributions to education in Indonesia is Muhammadiyah, through its active social enterprises in various educational activities. Purpose: This study aims to enhance the effectiveness of roleplaying as a learning model to improve students' understanding of Muhammadiyah's social enterprises in Grade XII at Muhammadiyah High School Bumiayu. Design/Methods/Approach: The research employs a qualitative approach, with data collected through observations, tests, and interviews. Findings: The study results indicate that role-playing is effective in helping students understand the material about Muhammadiyah's social enterprises. Students not only gain theoretical knowledge but also experience firsthand the values inherent in Muhammadiyah's work, such as hard work and sincerity. Despite challenges in implementation, such as doubts in playing characters, the method overall succeeded in increasing students' understanding and involvement in social activities. Research Implications/Limitations: Despite the challenges in its implementation, such as doubts in playing characters. Originality/Value: This research recommends using simpler materials to improve the effectiveness of learning in the future.